Diagnostic Value of Serum Pepsinogen Levels for Screening Gastric Cancer and Atrophic Gastritis in Asymptomatic Individuals: A Cross-Sectional Study - Tong, Yuling; Wang, Hongguang; Zhao, Yi; He, Xueqiang; Xu, Hongwei; Li, Hong; Shuai, Ping; Gong, Lirong; Wu, Hongbo; Xu, Hongzhi; Luo, Yinhu; Wang, Dong; et al. (Frontiers in Oncology, 2021)
Background: Pepsinogens (PGs) can be used for gastric cancer (GC) screening, but the cutoff levels vary among studies, and PG levels are influenced by numerous factors. To examine the diagnostic value of PG levels and Helicobacter pylori (Hp) status for GC and atrophic gastritis screening in asymptomatic individuals undergoing health checkup in China. Patients and Methods: This was a multicenter cross-sectional study of subjects who underwent health checkup from 10/2016 to 10/2018 at nine International Healthcare Centers in China. All participants underwent gastroscopy and pathological examination, serum PG, 13C-urea breath test, and/or Hp serological current infection marker rapid test, all on the same day. PG related parameters were analyzed in different Hp subgroups and regions. Results: The patients were grouped as non-atrophic (NAG, n=1590), mild-to-moderate atrophic (MAG, n=273), severe atrophic (SAG, n=49), and GC (n=10). The serum PG levels in these groups decreased with increasing pathological severity. In the same pathological groups, PGI and PGII levels were higher in the Hp-positive subgroup, while PGR (PGI/PGII ratio) was lower (P<0.05). The best cutoff values for atrophy diagnosis were PGI ≤73.1 ng/ml and PGR ≤9.8, for severe atrophy were PGI ≤63.9 ng/ml and PGR ≤9.09, for GC was PGR ≤4.7 (all P<0.05 and area under the curve >0.7). The cutoff points varied with Hp status and China regions. Conclusion: Serum PG levels might be used for the screening of gastric atrophic gastritis lesions. The results suggest that different cutoff values should possibly be used in different Hp status groups and geographical regions, but it will have to be validated in future studies. Future studies should also examine the value of PG levels for GC detection.